Ответ(ы) на вопрос:
Гость
[latex](x^2-4x+1)(x^2-4x+2)=12[/latex]
[latex](x^2-2*2x+4-3)(x^2-2*2x+4-2)=12[/latex]
[latex]((x-2)^2-3)((x-2)^2-2)=12[/latex]
пусть [latex](x-2)^2 = t[/latex]
[latex](t-3)(t-2)-12=0[/latex]
[latex]t^2+t \left( -2 \right) -3 t+6-12=0[/latex]
[latex]t^2-5 t-6 =0[/latex]
корни уравнения
[latex]t_1 = 6,\; t_2 = -1[/latex]
тогда
[latex](x-2)^2 = 6 \\ x-2 = \pm \sqrt{6} \\ x_{1,2} = 2 \pm \sqrt{6} [/latex]
и
[latex](x-2)^2 = -1[/latex] нет решения , т.к. [latex](x-2)^2 > 0[/latex]
Ответ:
[latex]x_{1} = 2 + \sqrt{6} [/latex]
[latex]x_{2} = 2 - \sqrt{6} [/latex]
Не нашли ответ?
Похожие вопросы